1988
DOI: 10.1104/pp.86.4.1252
|View full text |Cite
|
Sign up to set email alerts
|

Low Bundle Sheath Carbonic Anhydrase Is Apparently Essential for Effective C4 Pathway Operation

Abstract: The concentrating of inorganic carbon in bundle sheath cells is the key function of the unique reactions of the C4 pathway (13). The prime purpose of this process is to favor the carboxylation reaction catalyzed by Rubiscol at the expense of oxygenase activity, thereby eliminating photorespiration. Since CO2 as such is the substrate for Rubisco (5), and since it is the ratio of CO2 to 02 that determines the relative rates of carboxylase and oxygenase activities (1), it is the concentration of the CO2 component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
3

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 16 publications
3
66
3
Order By: Relevance
“…The values recorded here are much higher than those reported previously (4), due primarily to a consistent calculation error made in the earlier study. This did not affect the major conclusion of the earlier investigation, which was to show that bundle sheath cells contained a very low or negligible proportion of the CA activity in C4 leaves.…”
Section: Ca Activity In Leavescontrasting
confidence: 54%
See 1 more Smart Citation
“…The values recorded here are much higher than those reported previously (4), due primarily to a consistent calculation error made in the earlier study. This did not affect the major conclusion of the earlier investigation, which was to show that bundle sheath cells contained a very low or negligible proportion of the CA activity in C4 leaves.…”
Section: Ca Activity In Leavescontrasting
confidence: 54%
“…To sustain this process, atmospheric CO2 entering mesophyll cells must be rapidly converted to HCO3-and this reaction should rightly be regarded as the first step in C4 photosynthesis. Consistent with this concept is the fact that the CA of C4 leaves is very largely or exclusively confined to the cytosol of mesophyll cells (4,6,8), where PEP carboxylase is also located. In spite of this apparently critical role of CA in C4 photosynthesis, the quantitative aspects ofthe operation ofthis enzyme have been largely neglected.…”
supporting
confidence: 60%
“…Also, Maeda et al (2000) identified a gene (CmpA) that encodes a substrate-binding protein that can specifically bind to HCO 3 Ϫ in cyanobacteria, which may further aid in the diffusion of HCO 3 Ϫ and elevation of CO 2 in the carboxysome. In C 4 plants, CA is localized to the cytosol of mesophyll cells, where it supplies HCO 3 Ϫ to phosphoenolpyruvate carboxylase (Burnell and Hatch, 1988;Hatch and Burnell, 1990), and calculations show that without CA, the rate of photosynthesis is reduced. In fact, a recent study with transgenic Flaveria bidentis clearly supported a role for CA in the assimilation of CO 2 in C 4 plants (Ludwig et al, 1998).…”
mentioning
confidence: 99%
“…Bundle sheath cells contain little or no carbonic anhydrase, certainly less than 1% of total leaf activity (2). From this evidence and consideration of the earlier model (8), it was proposed that low bundle sheath cell carbonic anhydrase activity may be essential for effective operation of C4 pathway photosynthesis (2).…”
Section: Sensitivity Of the Model To Varying Assumptions And Parametersmentioning
confidence: 98%
“…The size and composition of such inorganic carbon pools would be affected by the pH of the various subcompartments and their permeabilities to bicarbonate. Uncertainty about the level and location of carbonic anhydrase is another complicating factor (2).…”
mentioning
confidence: 99%